2015
DOI: 10.3389/fnins.2015.00331
|View full text |Cite
|
Sign up to set email alerts
|

An array of highly flexible electrodes with a tailored configuration locked by gelatin during implantation—initial evaluation in cortex cerebri of awake rats

Abstract: Background: A major challenge in the field of neural interfaces is to overcome the problem of poor stability of neuronal recordings, which impedes long-term studies of individual neurons in the brain. Conceivably, unstable recordings reflect relative movements between electrode and tissue. To address this challenge, we have developed a new ultra-flexible electrode array and evaluated its performance in awake non-restrained animals.Methods:An array of eight separated gold leads (4 × 10 μm), individually flexibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 65 publications
2
54
0
1
Order By: Relevance
“…The resulting FBR and glial scar formation following implantation of the dextran coated MEAs was shown to be very minimal, with neurons infiltrating the dextran coating site following dissolution (Figure ,H1,H2). In a study by Agorelius et al, flexible MEAs were encased in a hard gelatin coating to aid in penetration, which would dissolve following MEA implantation. It was found that after several weeks following implantation, signals obtained from each MEA remained relatively stable, indicating that the gelatin coating prevented the MEA from becoming damaged during implantation.…”
Section: Microelectrode Array Modifications For Improving the Neural mentioning
confidence: 99%
“…The resulting FBR and glial scar formation following implantation of the dextran coated MEAs was shown to be very minimal, with neurons infiltrating the dextran coating site following dissolution (Figure ,H1,H2). In a study by Agorelius et al, flexible MEAs were encased in a hard gelatin coating to aid in penetration, which would dissolve following MEA implantation. It was found that after several weeks following implantation, signals obtained from each MEA remained relatively stable, indicating that the gelatin coating prevented the MEA from becoming damaged during implantation.…”
Section: Microelectrode Array Modifications For Improving the Neural mentioning
confidence: 99%
“…This formula is often used for compliant probes in the literature [7], [8] where is the mode of buckling, generally taken as 1 unless this mode is artificially restricted, E is the Young's Modulus of the probe's material, I the second moment of area, L the probes length and k the probes effective length. The value for k varies from 0.5 -2 depending on the boundary condition of the probe-tissue contact [9]- [11]. The column effective length factor k captures the degree to which each end of the column is constrained against movement.…”
Section: Regimes Of Neural Insertionmentioning
confidence: 99%
“…Figure c shows an optical image of the prepared insertion shuttle holding a flexible device (solar microcell array (3 × 6), each size: 600 µm × 800 µm, thickness: ≈4.1 µm) with the aid of a temporary adhesive (thickness: ≈30 µm) that is a mixture of gelatin, glycerin, and water. As gelatin extracted from animal proteins is known to be biocompatible and bioresorbable, it is widely used in drug delivery, medical glues, and hemostatic sponges, as well as coatings for implantable medical electrodes . Glycerin also known to be biocompatible is used as a plasticizer .…”
Section: Resultsmentioning
confidence: 99%